IMPROVING THE RESULTS OF MATH LEARNING THROUGH SCRAMBLE COOPERATIVE MODEL WITH THE APPROACH OF CONTEXTUAL TEACHING AND LEARNING MODEL - Ahmad Rustam; Muhammad Adli (JME (Journal of Mathematics Education), 2016)
This research is motivated by the desire of the author to enhance students' skills andlearning design that is not centered on the teacher. Thus, this study aims to improvestudents' mathematics learning outcomes through Scramble Cooperative LearningModel with Contextual Teaching and Learning (CTL) Approach at the class VIIIB SMPNegeri 1 Latambaga. The study was conducted on 28 April 2015 s / d dated May 28,2015. The subject of this research is class student of SMP Negeri 1 Latambaga VIIIB.This research is a Classroom Action Research conducted in two cycles with studyprocedures: (a) Conducting planning to implement the learning process, (b) Implementthe action in accordance with the plan, (c) Conducting observations of students andteachers during the process of the action takes place, (d) Conducting evaluations / teststo students in each end of the cycle, (e) to reflect and analyze the shortcomings andweaknesses during the first cycle for the plan of action on the second cycle. The resultsobtained are in action first cycle, the learning outcomes of students increased from anaverage score of initial tests before action is 68.25 into 77.71 or 78.12% with thepercentage of completeness that 25 of the 32 students received grades ?75, it this hasnot shown success according to defined indicators of success. In the second cycle of theresults obtained are as many as 27 students get value ?75 with an average value of83.15 or with a percentage of 84.37%. This means that the results of the research forcycle I and cycle II. It can be concluded that the results students grade VIIIB of SMPNegeri 1 Latambaga on material geometry through cooperative learning modelscramble with CTL approach that took effect on improvement of learning outcomes.